2022
DOI: 10.20525/ijrbs.v11i8.2073
|View full text |Cite
|
Sign up to set email alerts
|

Rethinking social interaction in English first additional language classrooms during the post Covid-19 era

Abstract: Social interaction among peers and teachers in English First Additional Language (EFAL) classrooms is a more significant predictor of communicative competence, which is the goal of any language program. During the Covid-19, there was a decline in social interaction among learners due to the sudden change from onsite to remote teaching and learning. This paper aimed to explore the effects of lack of social interaction in EFAL classrooms and how it can be enhanced during the 'New Normal'. This study was underpin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 31 publications
0
2
0
Order By: Relevance
“…As a result of this subjugation and exclusion, the isiXhosa language and its literature have suffered significant pandemonium in terms of distortion and erosion (to be illustrated later). The oppression of this language has allowed colonialists and apartheid agents to make mockery and humiliation of the language by creating government and administrative policies that sought to exclude the native speakers (amaXhosa) from taking full control of their language (Matiso and Makena, 2022). In other words, colonialism and apartheid disowned amaXhosa of their language.…”
Section: Introductionmentioning
confidence: 99%
“…As a result of this subjugation and exclusion, the isiXhosa language and its literature have suffered significant pandemonium in terms of distortion and erosion (to be illustrated later). The oppression of this language has allowed colonialists and apartheid agents to make mockery and humiliation of the language by creating government and administrative policies that sought to exclude the native speakers (amaXhosa) from taking full control of their language (Matiso and Makena, 2022). In other words, colonialism and apartheid disowned amaXhosa of their language.…”
Section: Introductionmentioning
confidence: 99%
“…Studies have shown that language teachers were already experiencing challenges in the implementation of recent language teaching methods, the Text-based Approach and Communicative Language Teaching. 13 In addition to the globally reported ineffective and inefficient language instructional practices, the outbreak of the coronavirus aggravated the situation. The COVID-19 pandemic elevated a method of language instruction that freed pupils from the grasp of language teachers and a constrained language classroom.…”
Section: Introductionmentioning
confidence: 99%